Evolution of dynamics of physico-chemical and mechanical properties of hydroxyapatite with fluorine addition and degradation stability of new matrices. (November 2022) - Erdem, Umit; Dogan, Deniz; Bozer, Büsra Moran; Karaboga, Seda; Turkoz, Mustafa Burak; Metin, Ayşegül Ülkü; Yıldırım, Gurcan
Abstract: This multidisciplinary study examined sensitively the change in the dynamics of main mechanical performance, stability of crystal structure, crystallinity quality, strength, corrosion resistance, biocompatibility, resistance to structural degradation/separations and mechanical durability features of hydroxyapatite (HAp) biomedical materials based on the fluorine addition and degradation process to guide future medical and dental treatment studies. In the study, the fluorine ions were used to be the dental coating, filling and supporting material for biologically or synthetically produced bone minerals. The general characteristic properties were investigated by means of standard spectroscopic, structural and mechanical analysis methods including RAMAN, SEM-EDS, TEM, Vickers micro-indentation hardness and density measurements. A time dependent release test was performed to evaluate possible fluorine ion release after the degradation process. It was found that the fundamental characteristic properties of HAp biomedical materials are noted to improve with the increase in the fluoride level up to 2% due much more stabilization of HAp crystal system. The combination of RAMAN spectra and powder XRD analyzes indicates that 2% addition level affects positively the formation velocity of characteristic HAP phase. Besides, fluorine doped HAp materials all exhibited the main characteristic peaks after degradation process. This is attributed to the fact that the fluorine ions enabled the hydroxyapatite to enhance the structural quality and stability towards the corrosion environment. However, in case of excess dopant level of 3% the degradation rates were obtained to increase due to higher contribution rate and especially electrostatic interactions. As for the surface morphology examinations, 2% fluorine added HAp with the highest density of 3.0879 g/cm 3 was determined to present the superior crystallinity quality (smallest grain size, best smooth surface, honeycomb pattern, regular shaped particles and densest particle distributions through the specimen surface). Conversely, the excess fluorine triggered to increase seriously degree of micro/macro porosity in the surface morphology and microscopic structural problems in the crystal system. Thus, the HAp doped with 3% was the most affected material from the degradation process. Additionally, the fluorine ion values read after the release process were quite far from the value that could cause toxic effects. Lastly, the optimum fluorine addition provides the positive effects on the highest durability, stiffness and mechanical fracture strength properties as a consequence of differentiation in the surface residual compressive stress regions (lattice strain fields), amplification sites and active operable slip systems in the matrix. Hence, the crack propagations prefer to proceed in the transcrystalline regions rather than the intergranular parts. Similarly, it was found that Vickers micro-indentation hardness tests showed that the microhardness parameters increased after the degradation process. All in all, the fluorine addition level of 2% was noted to be good choice to improve the fundamental characteristic properties of hydroxyapatite biomedical materials for heavy-duty musculoskeletal, orthopedic implant, biological and therapeutic applications in medicine and dentistry application fields. Graphical abstract: Image 1 Highlights: Effect of fluorine addition on dynamics of physico-chemical and mechanical properties. Spectroscopic, structural and mechanical analysis of novel biomedical compound. Optimum fluorine level of 2% for improvement in fundamental characteristic properties of HAp. Preference of crack propagations along transcrystalline regions with optimum fluorine ions. No toxic effects of fluorine doped HAp biomaterial.